MERANCANG PENDIDIKAN EKONOMI DAN BISNIS ISLAM DI DESA PURASEDA, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Miftakhul Anwar; Verlya Salsabila (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
Community service is a concrete manifestation of implementing the Tri Dharma of Higher Education, namely the aspect of community service. Through community service activities in Puraseda Village, Leuwiliang District, Bogor Regency, there is synergy between universities and the community as a form of knowledge democracy. The dissemination of knowledge to the community through community service activities aims to provide local communities with an understanding of the importance of education to help the government in making the nation smarter. The substance of this community service is to design Islamic economic and business education for the community. Community service is carried out through activities: educational workshops, educational seminars, provision of reading corners, and teaching. The results of community service provide an overview of how enthusiastic it is to increase public understanding, especially teachers and parents, about Islamic education, economics and business.